First evidence of resistance to pyrethroid insecticides in Italian Aedes albopictus populations 26 years after invasion. Issue 6 (21st February 2018) - Pichler, Verena; Bellini, Romeo; Veronesi, Rodolfo; Arnoldi, Daniele; Rizzoli, Annapaola; Lia, Riccardo Paolo; Otranto, Domenico; Montarsi, Fabrizio; Carlin, Sara; Ballardini, Marco; Antognini, Elisa; Salvemini, Marco; et al.
Abstract: BACKGROUND: Aedes albopictus has spread during the last few decades all over the world. This has increased significantly the risk of exotic arbovirus transmission (e.g. chikungunya, dengue, and Zika) also in temperate areas, as demonstrated by the Chikungunya 2007 and 2017 outbreaks in northeastern and central Italy. Insecticides are an important tool for limiting the circulation of these mosquito‐borne viruses. The aim of the present study was to address the gap in current knowledge of pyrethroid insecticide resistance of European Ae. albopictus populations, focusing on populations from Italy, Albania and Greece. RESULTS: Bioassays for resistance to permethrin (0.75%), α‐cypermethrin (0.05%) or deltamethrin (0.05%) were performed according to World Health Organization (WHO) protocols and showed reduced susceptibility (<90% mortality) of some Italian populations to permethrin and α‐cypermethrin, but not to deltamethrin. CONCLUSION: This study reports the first evidence of resistance to pyrethroids in adult Italian Ae. albopictus populations. Results refer to the season preceding the Chikungunya 2017 outbreak in central Italy and highlight the need to increase efforts to monitor the spread of insecticide resistance and the need to develop strategies to limit the spread of insecticide resistance, particularly in areas where extensive treatments have been carried out to contain disease outbreaks. © 2017 Society of Chemical Industry Abstract : The study reports the first evidence of resistance to pyrethroids in Italian Ae. albopictus populations, stressing the need to monitor insecticide resistance spread in order to maintain the effectiveness of insecticides.